Social capital and economic development : well-being in developing countries - Kelly, Thomas; Isham, Jonathan; Ramaswamy, Sunder (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2002)
Since the mid 1990s, theoretical and empirical research on how social capital affects well-being has blossomed in the field of economic development. Based on noted theoretical and empirical work in other social sciences, this concept is now becoming a vital new tool for economists. The chapters in this volume explore the challenges and opportunities raised by this concept for researchers, practitioners and teachers. The book is based upon a consistent, policy-based vision of how social capital affects well-being in developing countries. It includes a comparison of experimental and empirical evidence on social capital and a range of field-based evidence, from environmental to cultural to nation-building and on how investment in social capital can improve well-being. The contributions are from leading development economists as well as non-economic social scientists with expertise in this field.
Papers from the 21st Annual Conference on Economics Issues at Middlebury College, April 2000.
Includes bibliographical references and index.
oif 23/07/14, 19/02/2019
Loan
Keywords: Social capital (Sociology); Economic development $1 (BSocial aspectss; Developing countries $1 (BEconomic conditionss; Developing countries $1 (BSocial conditions $1 (BCongresses.s